Pernikahan Usia Dini dan Perspektifnya Menurut Hukum Islam di Desa Persiapan Berinding Kecamatan Kopang Kabupaten Lombok Tengah - Sri Hariati (Universitas Mataram, 2021)
The practice of early marriage is currently a common thing among the community, especially in rural areas where there is less information about the impact of this behavior. The purpose of this counseling is to provide education about the causes of early marriage and the impact it has, as well as its implications according to Islamic law. The method used in this counseling activity is using the lecture and discussion method. Based on the results of the evaluation carried out by the extension worker after the extension activity was completed, in general it could be said that the participants had only just learned the material presented. Lack of public awareness of deviant behavior carried out by men and women (early marriage), especially among adolescents who are not medically old enough, has resulted in this practice still occurring. So that it has become a joint task for parents in educating their children as well as possible both in the fields of religion and education so that our children avoid these actions.